El papel de las emociones positivas en el desarrollo de la Psicología Positiva - Alpízar Rojas, Harlen Yadira (2012)
This article presents a literature review aimed to investigate the role of positive emotions in Positive Psychology. The first part is an approach to the emergence and foundations of this branch of psychology; then it moves into the development of positive emotions and to know the roots of Positive Psychology. Later, it is made an exploration on the main positive emotions such as optimism, resilience, flow, happiness, creativity, humor, and emotional intelligence. Finally, the main criticism on this new model of positive psychology is reviewed as well as its future perspectives.